Three early modern Hebrew scholars on the mysteries of song - Harrán, Don (Studies in Jewish history and culture, 2014)
"In discoursing on music, three early modern Jewish scholars stand out for their originality. The first is Judah Moscato, who, as chief rabbi in Mantua, preached sermons, one of them on music: there Moscato presents music as a cosmic and spiritual phenomenon. The second scholar is Leon Modena, the foremost Jewish intellectual in early seventeenth-century Venice. Modena deals with music in two responsa to questions put to him for rabbinical adjudication, one of them an examination of biblical and rabbinical sources on the legitimacy of performing art music in the synagogue. Abraham Portaleone, the third scholar, treated music in a massive disquisition on the ancient temple and its ritual, describing it as an art correlating with contemporary Italian music. The introduction surveys the development of Hebrew art music from the Bible through the Talmud and rabbinical writings until the early modern era. The epilogue defines the special contribution of Hebrew scholars to early modern theory"--Provided by publisher